Implementation of Fuzzy Logic System for Motor Motion Generation Based on Electrooculogram / Nurul Muthmainnah Mohd Noor...[et al.] - Mohd Noor, Nurul Muthmainnah; Yusof, Ya’akub; Khairoll Anuar, Ikhmal Nazmi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2015)
Electrooculography (EOG) is a technique that sensed eye movement based on recording of the standing cornea-retinal potential that existing between the cornea and retina. This electrooculography signal is known as electrooculogram that can be used to control the human machine interface (HMI) such as a wheelchair motion. The aim of this project was to control the motor by using EOG signals. The signals of eye movements were acquired using the EOG circuit. These data were passed to the fuzzy logic controller that was developed using MATLAB. As a result, the two DC motors were able to operate according to the rules set of fuzzy logic using the eye signals as inputs. The limitation of this project was the fuzzy logic controller rules and the membership functions were developed using MATLAB and then converted into Arduino coding. The Arduino Mega 2560 acts as the interface between the EOG circuit and DC motors. Then, the fuzzy logic controller was integrated into Arduino Mega 2560 in order to control the motion of motor. Besides, there were four (4) subjects, two males and two female, selected for the EOG data acquisition.